The conditions under which farmers are likely to adapt their behaviour: A case study of private land conservation in the Cape Winelands, South Africa. (November 2015) - Honig, Maria; Petersen, Samantha; Shearing, Clifford; Pintér, László; Kotze, Inge
Highlights: We apply the AMPR framework to understand the enabling conditions of private land conservation. A case study of the Cape Winelands in South Africa is investigated. Two models illustrating the extrinsic and intrinsic motivations of participants for programme participation are presented. Abstract: Recent attention in environmental management research has been focussed on investigating how farm management responds to biodiversity conservation guidance provided through voluntary market-based mechanisms. There has been, however, very little research done on linking individual behavioural change theories with these conservation initiatives and moving beyond behavioural change to consider the role of learning, values and personal agency. There has also been little concern for the role of nonhuman agency in programme participation. This study aims to investigate the enabling conditions under which private biodiversity conservation is most likely to take place in agricultural landscapes by investigating the case of the WWF Biodiversity and Wine Initiative (BWI), an exemplar of 'successful' voluntary market-based conservation of the globally important Fynbos biome in the Cape Winelands of South Africa. Using a conceptual framework for pro-environmental behaviour, titled AMPR, this study argues that transitioning to more sustainable production in an agricultural context is constructed upon an in-depth understanding of the value system that underpins the motivational structure of the participant. Data were collected to assess participant's environmental awareness; motivation for programme participation; and the pathways for enabling implementation and the rewards for joining the BWI. The inter- and intra-connectedness between these four components (awareness, motivation, pathway and reward), and a list of success factors of and barriers to implementation are investigated. This study proposes two models using the AMPR framework that illustrate the extrinsic and intrinsic motivations of participants and how this impacts on programme participation, where nonhuman agency forms an explicit part of extrinsic motivation. Based on the two AMPR models, promising policy suggestions that could aid BWI in future are presented.